Dealing with de-selection from youth international football: A case study of English Premier League academies - Edwards, D.; Brannagan, P. M. (International Journal of Sports Science & Coaching, 2024)
This study investigated the perceptions of players and football club staff regarding de-selection from the youth international football environment. Prior research into youth football de-selection focuses on players` experiences of being released from their club environment; however, research is yet to understand the effect of de-selection from international football. The authors completed semi-structured interviews with 11 current youth international footballers and nine members of leadership staff from English Premier League youth academies, including academy directors, technical directors and heads of coaching. It was found that players had a strong identity as an international footballer and that once de-selected, it could be difficult to adapt to a change in status within their group at the club. The club staff also suggested that clubs do little to support the player once de-selected as although they perceive the player as being part of their development programme, they viewed international football as an area that was not their responsibility. Practical applications are discussed, including the need for clear justifications of de-selection and `after-care` solutions.